A South African research agenda to investigate the potential environmental, health and safety risks of nanotechnology - Musee, Ndeke; Brent, Alan; Ashton, Peter (South African Journal of Science, 2010)
The South African perspective on nanotechnology, recently articulated through its national strategy, envisages nanotechnology to provide solutions to some of the country’s key development challenges, such as the provision of safe water and the innovative delivery of health services. The adoption of nanotechnology is therefore being encouraged and nanomaterials are being manufactured on a small scale for research and development purposes. The national strategy places the most emphasis on supporting the design, manufacture, synthesis and characterisation of nanomaterials and developing human capital and infrastructure. However, South Africa has yet to develop a national research strategy to investigate the environmental, health and safety risks of nanotechnology. This paper provides a brief overview of the risk-related research challenges that have been reported internationally. These challenges form the basis of a research framework and a prioritised agenda is proposed to take research forward in the South African context. Ultimately, a greater understanding of the environmental, health and safety risks will help to ensure the long-term sustainability of nanotechnologies.